Hyper Suprime-Cam: System design and verification of image quality. (19th September 2017) - Miyazaki, Satoshi; Komiyama, Yutaka; Kawanomoto, Satoshi; Doi, Yoshiyuki; Furusawa, Hisanori; Hamana, Takashi; Hayashi, Yusuke; Ikeda, Hiroyuki; Kamata, Yukiko; Karoji, Hiroshi; Koike, Michitaro; Kurakami, Tomio; et al.
Abstract: The Hyper Suprime-Cam (HSC) is an 870 megapixel prime focus optical imaging camera for the 8.2 m Subaru telescope. The wide-field corrector delivers sharp images of 0${^{′′}_{.}}$ 2 (FWHM) in the HSC- i band over the entire 1${^{°}_{.}}$ 5 diameter field of view. The collimation of the camera with respect to the optical axis of the primary mirror is done with hexapod actuators, the mechanical accuracy of which is a few microns. Analysis of the remaining wavefront error in off-focus stellar images reveals that the collimation of the optical components meets design specifications. While there is a flexure of mechanical components, it also is within the design specification. As a result, the camera achieves its seeing-limited imaging on Maunakea during most of the time; the median seeing over several years of observing is 0${^{′′}_{.}}$ 67 (FWHM) in the i band. The sensors use p-channel, fully depleted CCDs of 200 μm thickness (2048 × 4176 15 μm square pixels) and we employ 116 of them to pave the 50 cm diameter focal plane. The minimum interval between exposures is 34 s, including the time to read out arrays, to transfer data to the control computer, and to save them to the hard drive. HSC on Subaru uniquely features a combination of a large aperture, a wide field of view, sharp images and a high sensitivity especially at longer wavelengths, which makes the HSC one of the most powerful observing facilities in the world.